Additional file 3 of Immune cell-resolved transcriptomics provides insights into the basis for variations of fish genetic resistance to viral disease - Thomas C. Clark (13318734) (2025)
Additional file 3. Table S3—Comparison of core conserved ISG expression in AP2 and B57 head kidney transcriptomes.